Optimizing growth hormone replacement therapy by dose titration in hypopituitary adults. - Drake, WM; Coyte, D; Camacho-Hübner, C; Jivanji, N; Kaltsas, G; Wood, D; Trainer, P; Grossman, AB; Besser, G; Monson, J (1998)
Although growth hormone (GH) replacement therapy is increasingly utilized in the management of adult hypopituitary patients, optimum dosing schedules are poorly defined. The use of weight-based or surface area-based dosing may result in overtreatment, and individual variation in susceptibility on the basis of gender and other factors is now being recognized. To optimize GH replacement and to explore further gender differences in susceptibility, we used a dose titration regimen, starting at the initiation of GH replacement therapy, in 50 consecutive adult-onset hypopituitary patients, and compared the results with those in 21 patients previously treated using a weight-based regimen. Titrated patients commenced GH 0.8 IU/day subcutaneously (0.4 IU/day if hypertensive or glucose tolerance impaired). Serum insulin-like growth factor I (IGF-I) was measured at 0, 2, 4, 6, 8, 10, and 12 weeks in all patients. Serum IGF binding protein 3 and acid labile subunit were measured at the same time points in 17 patients (8 male, 9 female). Patients were reviewed every 4 weeks and the dose of GH increased, if necessary, to achieve a serum IGF-I level between the median and the upper end of the age-related reference range. There was no significant difference between mean serum IGF-I at 2 and 4 weeks, or between 6 and 8 weeks, indicating that the full effects of a change in dose are evident within 2 weeks of that change. Maintenance doses were significantly higher in females than males [1.2 (0.8-2.0) vs. 0.8 (0.4-1.6) IU/day; median (range); P < 0.0001], and the median time to achieve maintenance dose was significantly shorter in males [4 (2-12) vs. 9 (2-26) weeks; P < 0.0001]. Median maintenance dose was lower overall than in a group of 21 patients initially commenced on GH using a weight-based dosing schedule, with subsequent adjustment of dose during clinical follow-up [1.5 (0.4-3.2) IU/day; P = 0.02]. Reduction in waist measurement and waist to hip ratio at 6 and 12 months was similar in females (P < 0.001) and males (P < 0.01). Well-being improved significantly after 3 months of GH therapy (14.2 +/- 5.9 vs. 7.4 +/- 4.5 SD; P < 0.0001), and there were no gender differences. Adult Growth Hormone Deficiency Assessment (AGHDA) scores at 6 months were similar to maintenance scores in patients commenced on weight-based regimens. Measurements of ALS and IGFBP-3 added no useful extra information to IGF-I in managing the dose titration. The practical scheme outlined for dose titration of GH replacement resulted in rapid achievement of lower maintenance doses than those achieved using conventional weight-based regimens without loss of efficacy. It was particularly important in female patients who demonstrated decreased overall sensitivity to GH and required higher doses to achieve the same effects as males. This constitutes the first report of a uniform titration regimen based on a defined target range of serum IGF-I in a large patient cohort.